Direction of Trade Statistics : June 2016. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2016)
This quarterly issue of Direction of Trade Statistics provides, for about 160 countries, tables with current data (or estimates) on the value of imports from and exports to their most important trading partners. In addition, similar summary tables for the world, industrial countries, and developing countries are included. The information on exports and imports by trading partners that countries report to the IMF varies in terms of frequency and currentness. Estimation occurs if a reporting country does not report trade with its partners for a specific period. Data are estimated for all partners and not for some of the partners. Country pages include lines for all partner countries that have been reported, estimated, or extrapolated. Summary tables for the world and areas are calculated from the data shown on the country page. They show the trade by a group of countries to and from the individual countries listed in the table.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet